Policy fairness in national integration: reactions of the new generation - Md. Yassin, Sulaiman; Dahalan, Dzuhailmi; Abdullah, Haslinda; Ismail, Ismi Arif; Hamzah, Azimi; Ahmad, Nobaya; Idris, Fazilah; Yee, Wendy Mei Tien; Banyan, Serit (TextRoad Publication, 2012)
This article discusses the reactions of the Malaysian youth regarding fairness of the national policy towards the inculcation of national integration. The extent to which national policy adopted for the sake of social harmony and multi-ethnic youth’s points of view were measured using a survey instrument with alpha value of .831. A total of 600 respondents were involved in this study. Students from secondary schools and higher education institutions (HEIs) in the Klang Valley were selected at random. The study found a positive reaction shown among the youth in Malaysia in relation to the practice of a fair policy towards strengthening national integration. The study also found that respondents' propensity to assess positively or otherwise of fairness in terms of the practice of policy towards national integration had no direct relationship with a number of selected demographic variables studied. In sum, the reaction of the new generation in Malaysia to conduct of public policy needs to be scrutinized by the government so that the objective to strengthen national integration can be achieved.